Pengaruh Profitabilitas dan Solvabilitas pada Ketepatwaktuan Publikasi Laporan Keuangan dengan Ukuran Perusahaan Sebagai Variabel Pemoderasi - Winarta, I Wayan; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p27, 2018)
This study aims to determine the effect of profitability and solvency on the timeliness of the publication of financial statements, and to determine whether or not the size of the company to moderate the effect of profitability and solvency on the timeliness of the publication of financial statements. S amples in this study were 48 mining company financial statements obtained by non-probability sampling technique with purposive sampling method. The analysis technique used in this research is Moderated Regression Analysis . Based on the results of the analysis it is known that the profitability variable has a positive effect on the timeliness of the publication of financial statements. Whereas solvability does not affect the timeliness of the publication of financial statements. The size of the firm is able to weaken the effect of profitability on timeliness, but can not moderate the effect of solvency on the timeliness of the publication of financial statements. Keywords: profitability, solvency, firm size, timeliness of financial report publication .